Propagation of Kab-dum Native Rice Cultivar (Oryza sativa) by Tissue Culture Techniques - รามสูตร, สุภาวดี (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2017)
In the past, Kab-dum (Oryza sativa) is a popular native rice cultivar grown in Pak Phanang. Nakhon Si Thammarat province. It is highly nutritional value and resistant to insect pests. Nowadays, there is a change in the environment and farmers prefer to grow rice instead of native rice cultivar. Native rice cultivar may be extincted in the future. The present study was used mature seeds to propagate by tissue culture technique. Mature seeds were cultured on Murashige and Skoog (MS) medium supplemented with various concentrations of 2,4-dichlorophenoxy acetic acid (2,4-D). After 1 month of culture, MS medium supplemented with 3 mg/L 2,4-D gave the highest percentage of survival rate at 100 and callus induction at 87±0.51% Callus was friable in texture. MS medium supplemented with 1 mg/L 2,4-D gave the highest percentage of compact callus induction at 20±0.50 %. significant difference at p ≤ 0.05. For shoot and root induction, MS medium supplemented with Benzyladenine (BA) at 1 mg/L BA and 0.1 mg/L Naphthaleneacetic acid (NAA) gave the highest percentage of shoot induction (16.78%), average number of shoots (2.40 shoots/explant), root induction (16.67%), average shoot height (11.74 cm./explant) and number of leaves (1.13 leaves/explant). However, MS supplemented with 1 mg/L BA and 0.5 mg/L NAA gave the highest number of roots at 2.51 roots/explant.